Choice and government intervention in housing markets - Cigdem, M.; Wood, Gavin (2012)
This article explores the changing role of Western governments in housing policy over the last few decades. The article begins by explaining how and why governments intervene in housing systems. According to the neoliberal critique, government intervention limits individual choice, stifles innovation, and distorts resource allocation with adverse consequences for efficiency. This critique has become increasingly influential in shaping housing policy. The article describes a range of policies that use market mechanisms and aim to increase choice and promote individual responsibility, principles that are at the heart of the neoliberal policy agenda. Finally, we offer some observations on recent housing policy developments. © 2012 Copyright © 2012 Elsevier Ltd All rights reserved..